2020
DOI: 10.1002/admi.202002098
|View full text |Cite
|
Sign up to set email alerts
|

Extending Lifetime of Water Droplets Using Mirror‐Nanoporous Surfaces

Abstract: to integrate versatile platforms, the low reagent/sample consumption, and the high throughput that can be achieved via automation. [5] To perform assays on such small liquid volumes (i.e., microliter range), especially in many bioapplications that require operation at physiological temperature (37 °C), it is critical to reduce the evaporation rate of the droplets to expand their lifetime. Physiological temperature is indeed necessary in the operation of a wide range of biochemical assays, such as in most cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Deviations from the classical D 2 -Law have been frequently observed, especially in droplet evaporation experiments in confined space [13] or in numerical simulations, e.g., evaporation of nanosize droplets and/or under supercritical conditions [14,15]. Among others, one reason accounting for the deviation is that the classical D 2 -Law is established for large open systems (L/D 0 1, L is the system size), which is not always the case in laboratory conditions, while simulations are inevitably limited to finite-size systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviations from the classical D 2 -Law have been frequently observed, especially in droplet evaporation experiments in confined space [13] or in numerical simulations, e.g., evaporation of nanosize droplets and/or under supercritical conditions [14,15]. Among others, one reason accounting for the deviation is that the classical D 2 -Law is established for large open systems (L/D 0 1, L is the system size), which is not always the case in laboratory conditions, while simulations are inevitably limited to finite-size systems.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, the classical D 2 -Law is established for large 3D systems, while a finite size and/or 2D system is encountered in many situations, which has not yet been systematically investigated. In experiments, examples of finite-size systems are the evaporation of a single droplet in microfluidic systems [13,31] or a dense collection of millimetric/micrometric droplets in a macroscale combustion chamber [32]. From the numerical simulation point of view, the system size is always limited by the computational cost [14], and 2D simulations are often considered for preliminary studies or model validation [29].…”
Section: Introductionmentioning
confidence: 99%
“…where 𝛾 is the interfacial tension, 𝜈 is the molar volume of solute, k is the Boltzmann constant, and 𝑇 is temperature (°K). 28 Evaporation of solvent in the confined area is slower than in the open areas, as Berli et al showed with sessile and confined water droplets, 29 which induces slower increase of 𝑆. At a certain time during evaporation leading to the nucleation step, the supersaturation is lower in the confined space than in the open space; it means that the nucleation barrier is higher in the confined area than in open areas at the same time.…”
mentioning
confidence: 99%
“…Even after the solution in the confined area is exposed to air, the much smaller surface to volume ratio of the solution in the confined area than that in open area ensures longer evaporation time. 29 Crystal growth is a kinetic process governed by transport of solute particles, surface diffusion, and equilibrium between adsorption and desorption. Those motions of solute particles in the confined space during evaporation are more restrained, which gives more stable crystal growth rates.…”
mentioning
confidence: 99%